Update on the Financing of the Fund's Concessional Assistance and Debt Relief to Low-Income Member Countries. (Policy Papers; Policy Paper ;, 2009)
This paper provides a semi-annual review of the status of financing for the Fund's concessional lending and debt relief to low-income countries (LICs). Since the last review, the Executive Board has approved comprehensive reforms of the Fund's concessional lending instruments and financing framework. This update is based on data available at end-August and also takes into account the implications of these reforms.